2022
DOI: 10.3390/insects13080706
|View full text |Cite
|
Sign up to set email alerts
|

Two New Species and a New Combination of the Subfamily Erythraeinae Based on Larval Stage (Acari: Trombidiformes: Erythraeidae) from China

Abstract: The species Eatoniana yangshuonicus (Haitlinger) comb. nov. is transferred from the genus Erythraeus to Eatoniana based on the basifemoral setal formula 2-2-1. Two new species, Eatoniana nanlingensis Xu and Jin sp. nov. and Erythraeus (Erythraeus) kunyuensis Xu and Jin sp. nov. are described and illustrated based on larvae. Eatoniana nanlingensis sp. nov. from the Oriental region (Guangdong Province), Er. (Er.) kunyuensis sp. nov. from the Palaearctic region (Shandong Province). An updated key to larval specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Noei and Honarmand (2020) corrected some mistakes in the original description and presented new metric data for E. gonabadensis (Ahmadi, Hajiqanbar and Saboori, 2012). Recently, Xu et al (2022) 1ω,2ζ,1z,26n 1ω,2ζ,1z,2ζ,1z,24n 1ω,2ζ,1z,2ζ,1z,24n 1ω,2ζ,1z,2ζ,1z,26n 1ω,2ζ,1z,26n 1ω,2ζ,1z,24n Ti I 2 φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z 1ω,2ζ,1z,26,2ζ,1z,…”
Section: Introductionmentioning
confidence: 99%
“…Noei and Honarmand (2020) corrected some mistakes in the original description and presented new metric data for E. gonabadensis (Ahmadi, Hajiqanbar and Saboori, 2012). Recently, Xu et al (2022) 1ω,2ζ,1z,26n 1ω,2ζ,1z,2ζ,1z,24n 1ω,2ζ,1z,2ζ,1z,24n 1ω,2ζ,1z,2ζ,1z,26n 1ω,2ζ,1z,26n 1ω,2ζ,1z,24n Ti I 2 φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z,14n 2φ,1ĸ,1z 1ω,2ζ,1z,26,2ζ,1z,…”
Section: Introductionmentioning
confidence: 99%
“…The subfamily Erythraeinae Robineau-Desvoidy includes 27 genera (Noei et al 2017;Saboori et al 2023), of which five genera have been reported in China (Xu et al 2022b). Hitherto, the genus Erythraeus Latreille, 1806 was reported worldwide except for Antarctica and comprises three subgenera (Mąkol & Wohltmann 2012;Roland & Gabryś 2020;Xu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, the genus Erythraeus Latreille, 1806 was reported worldwide except for Antarctica and comprises three subgenera (Mąkol & Wohltmann 2012;Roland & Gabryś 2020;Xu et al 2019). In China, five species belonging to the subgenus Erythraeus were described based on adult or larvae, and two species belonging to the subgenus Zaracarus were described based on larvae (Tseng et al 1976;Xu et al 2019Xu et al , 2022b. To date, there are seven species of the genus Erythraeus described from larval and postlarval stages, while five belong to the subgenus Erythraeus, and two are members of the subgenus Zaracarus (Karakurt et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation